Educação para a sexualidade na formação de professores na modalidade de ensino a distância: a utilização de um objeto educacional - Maia, Ana Cláudia Bortolozzi [UNESP]; Rodrigues, Olga Maria Piazentim Rolim [UNESP]; Melquiori, Lígia Ebner [UNESP]; Capellini, Vera Lúcia Messias Fialho [UNESP] (My University, 2014)
In inclusive school there are many students and some with disabilities. One of the dimensions of human development of all people's is the sexuality, although there are erroneous beliefs about the relationship sexuality and disability. Teachers must be prepared to deal with the sexuality of their students with disabilities in school, and proposals of education in the form of distance education has been an alternative to the training. This article relate an educational proposal for teachers, linked to a part of the activities undertaken in the discipline "Human Development and Family" on a course of specialization in Special Education in Distance Education mode. Describes an educational object named "Game: challenges and actions in school" , that presented four situations on behaviors involving sexuality of students: question about sexuality, masturbation in the classroom, dating from students and discrimination an obese colleague. In each one, there was potential actions to the teachers choose and, consequently, its unfolding. The choice of actions would lead to the end of a "teacher profile", offering reflections. Teachers reported positive unsolicited comments about the content of the game. It is concluded that the proposal is an important educational tool used in the Virtual Learning Environment that can assist in teacher training courses in sexuality education.

Na escola inclusiva convivem estudantes diversos e alguns, com deficiência. Uma das dimensões no desenvolvimento humano de todas as pessoas é a sexualidade, embora existam crenças errôneas sobre a relação sexualidade e deficiência. Professores/as devem estar preparados para lidar com a sexualidade de estudantes com deficiência na escola, e, propostas de capacitação na modalidade de Educação a Distância (EaD) têm sido uma alternativa de formação. Este artigo apresenta uma proposta de educação para professores, vinculada a uma parte das atividades realizadas na disciplina “Desenvolvimento Humano e Família” de um curso de Especialização em Educação Especial, na modalidade EaD. Descreve-se um objeto educacional denominado “Jogo: desafios e ações na escola”, em que, continha quatro situações sobre comportamentos envolvendo a sexualidade de estudantes: pergunta sobre sexualidade, masturbação na sala de aula, namoro do pátio da escola e discriminação de uma colega obesa. Em cada uma delas, havia possíveis ações para os/as professores escolherem e, em decorrência, seus desdobramentos. A escolha das ações levaria ao final a um “perfil docente”, oferecendo reflexões. Os docentes registaram comentários espontâneos positivos sobre o conteúdo do jogo. Conclui-se que essa proposta foi um importante instrumento pedagógico utilizado no Ambiente Virtual de Aprendizagem que pode auxiliar na formação de professores/as em cursos de educação para a sexualidade.
Keywords: sexual education; inclusion; disability; distance education; educational object; educação sexual; inclusão; deficiência; educação a distância; objeto educacional